2017
DOI: 10.1038/cddis.2017.350
|View full text |Cite
|
Sign up to set email alerts
|

Di (2-ethylhexyl) phthalate exposure impairs meiotic progression and DNA damage repair in fetal mouse oocytes in vitro

Abstract: Di (2-ethylhexyl) phthalate (DEHP), is the most common member of the class of phthalates that are used as plasticizers and have become common environmental contaminants. A number of studies have shown that DEHP exposure impacts reproductive health in both male and female mammals by acting as an estrogen analog. Here, we investigated the effects of DEHP on meiotic progression of fetal mouse oocytes by using an in vitro model of ovarian tissue culture. The results showed that 10 or 100 μM DEHP exposure inhibited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
44
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 72 publications
(53 citation statements)
references
References 42 publications
5
44
2
1
Order By: Relevance
“…DEHP, an environmental contaminant, is extensively used in various applications and almost found everywhere in the environment . More and more studies indicate that DEHP does harm to mammalian reproductive system . Particularly, DEHP exposure is associated with the changes in female ovarian function, as well as increased risk of endometriosis, preterm delivery, and various pregnancy complications .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…DEHP, an environmental contaminant, is extensively used in various applications and almost found everywhere in the environment . More and more studies indicate that DEHP does harm to mammalian reproductive system . Particularly, DEHP exposure is associated with the changes in female ovarian function, as well as increased risk of endometriosis, preterm delivery, and various pregnancy complications .…”
Section: Discussionmentioning
confidence: 99%
“…Researches have reported that DEHP exposure on human ranges from 3 to 30 μg/kg/d . To simulate the concentration in vivo, the experimental concentration of DEHP was selected to be 10 or 100 μmol/L according to the previous experiments in vitro . Equal concentrations of solvents were added to the culture medium as the control group.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations